Sosialisasi Budidaya Microgreens Skala Rumah Tangga bagi Masyarakat di Kelurahan Pandeyan Yogyakarta - Restiani, Ratih (Pelita: Jurnal Pengabdian kepada Masyarakat, 2022)
Microgreens have emerged as a new trend in urban farming due to more practice, efficiency, affordable, short periods of cultivation, and highly nutrition than other types of urban farming methods. The increase of physical development in Pandeyan, ??Yogyakarta due to the increase in population has caused a decrease in the area for plant cultivation. One of the solutions to overcome this problem is through the socialization of household-scale microgreens cultivation. Therefore, this socialization aimed to enhance the knowledge of the Pandeyan community regarding the definition of microgreens, types of plants that can be cultivated, benefits, stages of cultivation, and business opportunities. The socialization was delivered in the form of a webinar on Tuesday, 30th November 2021 using Zoom platform, with a total 32 of participants. This activity is divided into 3 stages: introduction, transfer of knowledge, and discussion. Based on the evaluation, this activity has succeeded in increasing the community's knowledge about microgreens, their benefits, and the stages of microgreens cultivation based on the high enthusiasm of the community during the discussion session.